2021
DOI: 10.1002/adma.202103646
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Point‐of‐Care Testing Technologies for Human Acute Respiratory Virus Detection

Abstract: system leading to respiratory tract infections (respiratory viruses, RVs). These diseases have the highest morbidity and fatality rates among acute infectious diseases and have caused a series of pandemics throughout human history. The first recorded RV occurred in 1200 BC, and subsequent major RVs have included the 1918 influenza virus, [1] severe acute respiratory syndrome coronavirus (SARS-CoV-1), [2][3][4][5] 2009 swine flu (H1N1), [6] Middle East respiratory syndrome (MERS) coronavirus, [7,8] and severe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 335 publications
(366 reference statements)
0
82
0
2
Order By: Relevance
“…Considering oxidative stress contributes to the pathogenesis of MIR injury, we measured the changes of oxidative stress-associated marker molecules including malondialdehyde (MDA) and superoxide dismutase (SOD) upon SGI treatment. The results showed that SGI downregulated the MDA level and upregulated the SOD activity both in the serum and in the myocardial tissue (Figure S2 e-f, h-i), suggesting that SGI attenuated the oxidative stress under MIR condition [ 33 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering oxidative stress contributes to the pathogenesis of MIR injury, we measured the changes of oxidative stress-associated marker molecules including malondialdehyde (MDA) and superoxide dismutase (SOD) upon SGI treatment. The results showed that SGI downregulated the MDA level and upregulated the SOD activity both in the serum and in the myocardial tissue (Figure S2 e-f, h-i), suggesting that SGI attenuated the oxidative stress under MIR condition [ 33 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…At present, a growing number of countries have moved into a post-pandemic phase, i.e., the overall spread of COVID-19 has been controlled, but intermittent small-scale outbreaks still occur ( Jin et al, 2021 ). COVID-19 is a respiratory infectious disease (RID) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ( Zhang et al, 2022a , Zhang et al, 2022b ). RID poses a huge threat to the population and public health, and recent studies have found that the loss of life expectancy due to RID stood at 1.29 years in 2017 globally ( Huang and Guo, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has several drawbacks in point-of-care detection: namely, it is time-consuming and demands expensive instrumentation [ 10 ]. Thus, many alternative methods have been developed for simple and rapid point-of-care detection [ 11 , 12 ]. For the purpose of viral RNA detection, new techniques for rapid isothermal amplification, which is pivotal in rapid point-of-care detection, have been realized using, for example, recombinase polymerase amplification (RPA) [ 13 15 ], rolling circle amplification (RCA) [ 16 , 17 ], and loop-mediated isothermal amplification (LAMP) [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%